(untitled) (Simbiótica. Revista Eletrônica, 2025)
Based on Edgar Morin’s reflections and the ideas of complex thinking, this article deals with the production of knowledge and the reconstitution of epistemologies using the metaphor developed by Hubert Reeves (2002) of the “artisans of the eighth day,” which defines subjects as producers of knowledge capable of creating new forms of sociability in the here and now. The study problematizes the hegemonic paradigms that structure knowledge and proposes collective utopia as a vector for the invention of plural, emancipatory, and integral epistemologies. Through a theoretical-conceptual approach, this work highlights the importance of creativity and hope as intercommunicators of knowledge. It defends the urgency of dialogical practices that foster diversity, with the aim of building more supportive communities. Rethinking the role of knowledge for social transformation is one of the tasks to be accomplished in order to achieve these ends